Lower limb asymmetry during the skeleton push start - Muckelt, M.; Needham, L.; Preatoni, E.; Colyer, S. (ISBS Proceedings Archive (Michigan), 2022)
The aim of this study was to identify the presence and performance implication of asymmetry within the skeleton push start. Motion data were captured on 13 international skeleton athletes, using a custom 9-camera computer vision system. 6 maximal effort pushes were captured allowing the reconstruction of a 0-15 m push. Intra-limb differences for spatiotemporal variables and the change in velocity (dV) across a step were analysed. A negative relationship existed between 5 - 15 m split time and dV across a stride. Athletes who maximise their velocity across a stride were more likely to perform well in the skeleton push start. Though athletes employed different strategies based on inside and outside leg dV to achieve their performance outcome.